Market Structure, Durability, and Maintenance Effort - Schmalensee, Richard (Review of Economic Studies, 1974)
Journal Article Market Structure, Durability, and Maintenance Effort Get access Richard Schmalensee Richard Schmalensee University of California, San Diego, and Catholic University of Louvain Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 2, April 1974, Pages 277–287, https://doi.org/10.2307/2296716 Published: 01 April 1974